Implementasi Asas Nemo Plus Juris Terkait Perbuatan Hukum Atas Tanah di Hadapan PPAT (Studi Kasus Putusan Mahkamah Agung Nomor 2678 K/ PDT/ 2015) - Ritonga, Syarifah Hasna; Yamin, Muhammad; Zaidar, Zaidar; Suprayitno, Suprayitno (Mahesa Research Center, 2023)
The study explores the implementation of the Nemo Plus Juris principle by Land Deed Officials (PPAT) in Indonesia, focusing on its role in overseeing the transfer of land rights. Analyzing a case study, the research investigates PPAT's responsibilities, the legal certainty ensured by the Nemo Plus Juris principle in land transactions, and the legal analysis of a specific court decision (No. 2678/K/Pdt/2015) related to this principle. Employing a normative juridical approach, the study draws on court decisions and legal literature. PPAT's accountability aligns with Government Regulation No. 24 of 1997, emphasizing adherence to legal provisions during land rights transfer. The Nemo Plus Juris principle, highlighted in Article 37(1) of the regulation, invalidates transfers by unauthorized entities, underscoring the significance of valid deeds in legitimizing land transactions. The court decision recognizes the principle's importance, confirming rightful ownership based on evidence from PPAT-issued Sale and Purchase Deeds. This study contributes to clarifying PPAT's adherence to legal norms and understanding judges' considerations in upholding the Nemo Plus Juris principle, essential in land ownership disputes.